2008
DOI: 10.17221/1865-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships of growth hormone AluI polymorphism, insulinresistance, milk production and reproductive performance in Holstein-Friesian cos

Abstract: Healthy multiparous Holstein-Friesian cows (n = 22, parity: 2-4) from a large-scale dairy herd in Hungary were subjected to an intravenous glucose tolerance test 10-15 days after calving. AluI genotype of growth hormone, several plasma metabolites and metabolic hormones were determined, and current and previous lactation yields were recorded. We also used the Revised Quantitative Insulin Sensitivity Check Index (RQUICKI) and its modified version (RQUICKI BHB ) for the estimation of peripheral insulin sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 45 publications
6
41
0
3
Order By: Relevance
“…Serum insulin values showed to be decreased in the post-partum period, as well. Insulin plays a role in the adaptation of metabolism in dairy cows during the transition period, particularly in terms of nutrient redistribution and partitioning towards the mammary gland during early lactation (insulin resistance) [28]. The decrease in insulin levels found during post-partum is consistent with previous studies which reported high insulin levels before parturition, followed by a gradual decrease from 10 days before parturition remaining relatively low throughout lactation [28].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Serum insulin values showed to be decreased in the post-partum period, as well. Insulin plays a role in the adaptation of metabolism in dairy cows during the transition period, particularly in terms of nutrient redistribution and partitioning towards the mammary gland during early lactation (insulin resistance) [28]. The decrease in insulin levels found during post-partum is consistent with previous studies which reported high insulin levels before parturition, followed by a gradual decrease from 10 days before parturition remaining relatively low throughout lactation [28].…”
Section: Discussionsupporting
confidence: 88%
“…Insulin plays a role in the adaptation of metabolism in dairy cows during the transition period, particularly in terms of nutrient redistribution and partitioning towards the mammary gland during early lactation (insulin resistance) [28]. The decrease in insulin levels found during post-partum is consistent with previous studies which reported high insulin levels before parturition, followed by a gradual decrease from 10 days before parturition remaining relatively low throughout lactation [28]. Lower glucose and insulin levels found during the post-partum period relative to the pre-partum period may be due to a decreased responsiveness of pancreatic β-cells to a state of hyperglycemia, caused by factors which inhibit the release of insulin [7].…”
Section: Discussionmentioning
confidence: 99%
“…All metabolites and hormones were determined with commercial kits adapted for assaying bovine and ovine plasma samples in our lab (Meikle et al, 2004;Kulcsar et al, 2006;Balogh et al, 2008). Glucose was measured using the GOD-POD reaction (Glucose kit, Cat.…”
Section: Handling Of Blood Samples Laboratory and Statistical Procedmentioning
confidence: 99%
“…As a result, low levels of insulin, IGF-1, leptin, thyroxine (T 4 ), and 3,3' ,5-triiodothyronine (T 3 ) are measured in the blood. These endocrine consequences are clearly demonstrated in peri-parturient and postpartum dairy cows (Pethes et al, 1985;Sartin et al, 1988;McGuire et al, 1991;Harmon, 1992;Bauman, 2000;Kadokawa et al, 2000;Kahl et al, 2000;Meikle et al, 2004;Balogh et al, 2008;Bossaert et al, 2008;Lucy, 2008), and during late gestation also in twinpregnant, hyperketonemic ewes (Henze et al, 1998;Van Saun, 2000;Kulcsar et al, 2006).…”
mentioning
confidence: 99%
“…The different indices provide similar but not identical results, so that more than one index should be used (Muniyappa et al, 2008). Some of these indices have already been applied in studies on dairy cows (Holtenius and Holtenius, 2007;Balogh et al, 2008;Kerestes et al, 2009) and, in addition, some studies reported similar changes in the values for QUICKI, RQUICKI, RQUICKI-BHB and parameters of glucose tolerance tests (Balogh et al, 2008;Bossaert et al, 2009). However, as a consequence of the differences in glucose metabolism between dry and lactating cattle, due to the processes involved in nutrition partitioning for milk production, these indices should not be used for comparisons throughout the periparturient period and therefore are only used here for comparisons between the two management systems at the same stage.…”
Section: Discussionmentioning
confidence: 99%